Different teaching methodologies in quality control class (Research, Society and Development, 2020)
Using different methodologies can bring benefits for students' learning, promoting transformations in the teaching method, which is the great current challenge. In this sense, active methodologies are presented as a tool to promote the teaching-learning process, which inserts students as autonomous in their search for knowledge. Thus, the objective of this study was to evaluate the perception of students of Chemical Engineering and Food Engineering courses regarding the use of different teaching methodologies in two classes taught. For this, videos, question and answer games and current news linked to the study topic were used to promote the active participation of academics who were assessed with the application of an online questionnaire. As a result, it was observed that most academics considered it necessary to use different methodologies, such as those used in the class in question, and that this promoted greater understanding and motivation in relation to the content studied, showing that students yearn for changes to favor teaching-learning.